Constraint logic programming with a relational machine - Gallego Arias, Emilio Jesús; Lipton, James; Mariño, Julio (Formal aspects of computing, 2017)
We present a declarative framework for the compilation of constraint logic programs into variable-free relational theories which are then executed by rewriting. This translation provides an algebraic formulation of the abstract syntax of logic programs. Logic variables, unification, and renaming apart are completely elided in favor of manipulation of variable-free relation expressions. In this setting, term rewriting not only provides an operational semantics for logic programs, but also a simple framework for reasoning about program execution. We prove the translation sound, and the rewriting system complete with respect to traditional SLD semantics.